Edukasi Kesehatan Perilaku Hidup Bersih Dan Sehat Untuk Anak Sekolah Minggu HKBP PPGS - Veronica Paula; Yenni Ferawati Sitanggang; Deborah Siregar; Evanny Indah; Dina Valentina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Clean and healthy life behavior (PHBS) is all health behavior that is done on awareness so that family members or family can help themselves in the field of health and play on active role in health activities in the community. Clean and healthy life behavior has 12 indicators; childbirth assisted by health personnel, exclusive ASI, weighing children every month, using clean water, washing hands with water and soap, using healthy latrines, eradicating larvae at home once a week, eating fruit and vegetables each day, do physical activity every day and do not smoke in the house. School-age children as the next generation of the nation should be given health education to provide good habits that improve the health of children and their families. Two things that was focused from those indicators were health education about a helathy teeth and mouth as well as hand hygiene. The result revealed that from 29 Sunday school children, there were 17 children (58.62%) had a healthy and clean tooth, four children (13.79%) undergone a tooth filling, six children were recommended to come to a dental clinic for futher treatment of their cavity and two children (6.89%) had their tooth extraction. From the result, it can be seen that more than half children have a healthy and good tooth.